Analisis Faktor yang Mempengaruhi Kredibilitas Kinerja Perusahaan - Brata, Zaini Danu; M. Ratna Sari, Maria (E-Jurnal Akuntansi; Vol 28 No 3 (2019)DO - 10.24843/EJA.2019.v28.i03.p11, 2019)
The purpose of this study is to determine the effect of the application of Good Corporate Governance, Ownership Structure, and Company Size on Company Performance. Several factors This study aims to determine the effect of Good Corporate Governance (CGPI) on the Performance of Companies listed on the IDX for the period 2013-2017. The research population is a company that is listed on the Indonesian stock exchange and at the same time follows the ranking of the Corporate Governance Perception Index with sample selection through a purposive sampling method. There are 55 companies that meet the criteria as research samples. The results show that Good Corporate Governance has a significant positive effect on company performance, Managerial Ownership has a positive and significant effect on company performance, Institutional Ownership does not have a positive and significant effect on Company Performance, Company Size positive and significant effect on Financial Performance. Keywords : Good corporate governance, ownership structure, company size, company performance.